2003
DOI: 10.3341/kjo.2003.17.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-Induced Cell Death in a Human Retinal Pigment Epithelial Cell Line, ARPE-19

Abstract: The loss of retinal pigment epithelium (RPE) with aging is related to age-related macular degeneration (AMD). This study was conducted to investigate the mechanism of hydrogen peroxide (H2O2) induced cell death in a human retinal pigment epithelial cell line, ARPE-19. Hydrogen peroxide was added at different concentrations to ARPE-19 cells and cultured. The cytotoxicity was assayed by mitochondrial function using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) testing. The patterns of cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 1 publication
4
41
0
2
Order By: Relevance
“…2). The absorbance of H 2 O 2 at 800 ”mol/L by MTT assay was significantly lower than that of the control group (P<0.05), indicating that the dosage of H 2 O 2 to induce a half-value of MC3T3-E1 apoptosis was around 800 ”mol/L, which is close to the previously reported value (600 ”mol/L) by Kim et al (2003).…”
Section: Mc3t3-e1 Apoptosis Induced By H 2 O 2 At Various Concentrationssupporting
confidence: 80%
“…2). The absorbance of H 2 O 2 at 800 ”mol/L by MTT assay was significantly lower than that of the control group (P<0.05), indicating that the dosage of H 2 O 2 to induce a half-value of MC3T3-E1 apoptosis was around 800 ”mol/L, which is close to the previously reported value (600 ”mol/L) by Kim et al (2003).…”
Section: Mc3t3-e1 Apoptosis Induced By H 2 O 2 At Various Concentrationssupporting
confidence: 80%
“…The eye is a highly oxidative stressed tissue. In normal human eyes, H 2 O 2 levels in the aqueous humor have been reported to be in the range of 14-31 mM, whereas under pathological conditions such as cataracts, H 2 O 2 levels can range from 33 to 500 mM in the aqueous humor [36][37][38] at this pathological range stimulating apoptosis in RPE cells in vitro and shown high numbers of apoptotic RPE cells in postmortem AMD eyes [23,39,40]. Because the implanted RPE will remain in the highly oxidative stressed environment of an AMD patient's eye, we simulated those pathological conditions with high dosages of H 2 O 2 to treat hESC-RPE cells in vitro and compared the resistance to the oxidative stress between the polarized and nonpolarized RPE cells.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of RPE cell death in response to oxidative stress and in GA has been controversial. Apoptosis was suggested as a major mechanism of RPE cell death, even though several studies suggested necrosis as mechanism of RPE cell death in vitro (9,10) and in vivo (11,12). Necrosis used to be considered a passive and unregulated form of cell death.…”
mentioning
confidence: 99%